2011
DOI: 10.5897/ajpp10.282
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the combination of herbal extracts and a silicone derivative in the treatment of hypertrophic scar formation after burn injury

Abstract: The development of hypertrophic scars is an unsolved problem in the process of wound healing. The objective of this research was to study the efficacy of the combination of herbal extracts and a silicone derivative in a gel preparation (Cybele ® Scagel) on the treatment of deep second degree burns after complete epithelialization. Sixty-three patients were enrolled in this study. One wound area larger than 10 × 10 cm was selected from each patient to receive treatment with Cybele ® Scagel. Patients were observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Allantoin is known to have supportive effects on the primary and secondary wound healing process (Hosnuter et al 2007;Koc et al 2008;Karagoz et al 2009;Muangman et al 2011). It was shown that heparin, cepae extract and allantoin mixtures decrease dermal scar formation more effectively than steroids (Beuth et al 2006;Temiz et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allantoin is known to have supportive effects on the primary and secondary wound healing process (Hosnuter et al 2007;Koc et al 2008;Karagoz et al 2009;Muangman et al 2011). It was shown that heparin, cepae extract and allantoin mixtures decrease dermal scar formation more effectively than steroids (Beuth et al 2006;Temiz et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Allantoin is also a counterirritant that helps alleviate skin irritation. Allantoin has emollient and soothing properties and can reduce inflammation (Hosnuter et al 2007;Campanati et al 2010;Muangman et al 2011).…”
mentioning
confidence: 99%
“…It may be because A. vera extract is constituted in both gels. The A. vera extract has a natural cyclooxygenase II (COX-2) inhibiting property, which decreases pain and inflammation so it can improve the feeling of pain in both groups [6,12]. Moreover, this study was controlled by using only topical preparation so the efficacy of treatment might not be sufficient for those patients who have deeper wounds and more aggressive scar and it may be necessary to include other combination therapies such as pressure garment and surgical scar correction.…”
Section: Discussionmentioning
confidence: 94%
“…The early wound closure by epithelialization might decrease the chance of hypertrophic scar formation. It contains salicylate compound, which can decrease pain and itch [12]. Although it has an effect on vascularity, itch and pain parameters, there are other compounds in silicone plus herbal extract gel in study group, which can improve the effect on itch, pain and hypervascular conditions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation